THE QUALITY OF ACCOUNTING INFORMATION SYSTEM PERFORMANCE IN DENPASAR CITY VILLAGE OFFICES - Luh Komang Merawati; Ida Ayu Nyoman Yuliastuti; Ni Luh Putu Suwandewi (AKUNTANSI DEWANTARA, 2023)
This study aims to examine user involvement, personal technical skills, user communication, organizational size and information quality on the performance of accounting information systems (AIS) at village offices in Denpasar City. The population in this study were employees at village offices throughout Denpasar City and obtained 64 employees as sample using purposive sample method. Data analized with multiple linear regression analysis. The results showed that user involvement in the development of AIS, user communication and information quality has a positive effect on AIS performance, while personal technical skills and organizational size had no effect on AIS performance.